2012
DOI: 10.1371/journal.pone.0042019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Leucocyte Depletion and Prion Reduction Filters on TSE Blood Borne Transmission

Abstract: The identification in the UK of 4 v-CJD infected patients thought to be due to the use of transfused Red Blood Cell units prepared from blood of donors incubating v-CJD raised major concerns in transfusion medicine. The demonstration of leucocyte associated infectivity using various animal models of TSE infection led to the implementation of systematic leuco-depletion (LD) of Red Blood cells concentrates (RBCs) in a number of countries. In the same models, plasma also demonstrated a significant level of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…The infectious titers that we measured in the whole blood used for the transfusion experiment were lower than 10 ID/ml. These infectious titer values are similar to those established in a previous study in similar animals (VRQ/VRQ sheep) infected with the same scrapie isolate (12,13). These data complement and expand the previously reported results and confirm that the risk of transmitting prion disease by blood transfusion is higher than expected from the measurement of blood infectious titers by the intracerebral inoculation of mice (12).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The infectious titers that we measured in the whole blood used for the transfusion experiment were lower than 10 ID/ml. These infectious titer values are similar to those established in a previous study in similar animals (VRQ/VRQ sheep) infected with the same scrapie isolate (12,13). These data complement and expand the previously reported results and confirm that the risk of transmitting prion disease by blood transfusion is higher than expected from the measurement of blood infectious titers by the intracerebral inoculation of mice (12).…”
Section: Discussionsupporting
confidence: 90%
“…This value is lower than the current leukoreduction standard target for red blood cell concentrate (10 6 WBC per unit). This is a likely explanation for the imperfect efficacy of leukoreduction to prevent prion disease transmission by RBC transfusion in sheep TSE models (13,23). Under the hypothesis that the sheep scrapie model is relevant for the evaluation of the vCJD transmission risk by the transfusion route in humans, these results support the contention that RBC leukodepletion is insufficient in the prevention of vCJD blood-borne transmission.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Immunological detection of PrP Sc in peripheral tissues The infectivity studies have shown that prion proteins occurred in low amounts in the peripheral tissues, such as lymphoid organs and blood, 32 already at early stages of the disease, e.g. during the pre-symptomatic period.…”
Section: Prion Volume 7 Issuementioning
confidence: 99%